No limite da dor: o vislumbre do paciente-limite no âmbito da metapsicologia freudiana - Carrara, Sonia Regina Alves (2013)
The clinical diagnosis of a borderline case is a relatively new concept. It was not yet defined or known at the time Freud was working on his famous 1895 Project, creating the Metapsychology. In this dissertation, we analyze briefly the model of the psychic apparatus proposed by Freud in the Project, and demonstrate that it already included the conceptual bases that can be used to explain the psychic workings of those nowadays called borderline cases. The model developed in the Project, does not correctly describe the neurological apparatus known to modern science. However, it certainly served Freud well as a basis for many of his conclusions and developments leading to the creation of Psychoanalysis